The Video Cenferencing Learning Environment In Distance Education A Study Of The Interaction Pattern. - Majid, Omar; A Rahman, Zuraidah; A Ghani, Noraida; Saw, Kim Guan; M Idrus, Rozhan; Atan, Hanafi (2006)
This article reports on the study undertaken to elucidate the pattern of interactions in the Video Conferencing Learning Environment (VCLE) used as a course delivery mechanism in distance learning.